Oxide-mediated mechanisms of gallium foam generation and stabilization during shear mixing in air. Issue 25 (21st May 2020) - Kong, Wilson; Shah, Najam Ul Hassan; Neumann, Taylor V.; Vong, Man Hou; Kotagama, Praveen; Dickey, Michael D.; Wang, Robert Y.; Rykaczewski, Konrad
Abstract : The fracturing and incorporation of liquid gallium surface oxides during shear mixing in air enables the stabilization of air bubbles within gallium which leads to the formation of a room-temperature liquid metal foam. Abstract : Foaming of gallium-based liquid metals improves their processability and—seemingly in contrast to processing of other metal foams—can be achieved through shear-mixing in air without addition of solid microparticles. Resolving this discrepancy, systematic processing–structure–property characterization demonstrates that many crumpled oxide particles are generated prior to air bubble accumulation.